Construction and application of a time-saving mode in China for the treatment of acute ischemic stroke - Yan, Yazhou; Du, Li; Shangguan, Xiu; Li, Lujun; Chi, Yuxiang; Wang, Yu; Cheng, Shuai; Huang, Qinghai; Pan, Yuan; Xin, Tao (Frontiers in Neurology, 2024)
Objective To explore the construction and application in the practice of green channel in No. 971 Naval Hospital of PLA (No. 971 Hospital mode) for the treatment of acute ischemic stroke (AIS). Methods This retrospective study involved a cohort of 694 suspected stroke patients from December 2022 to November 2023 undergoing emergency treatment for stroke at our institution. Among them, 483 patients were treated with standard green channel (the control group), and 211 patients adopted the No. 971 Hospital mode for treatment (the study group). The biggest difference between the two groups was that the treatment process started before admission. We compared the effectiveness of the emergency treatment between the two groups and the thrombolysis treatment. Results Compared with control group, the accuracy rate of determining stroke and the rate of thrombolysis were significantly higher (p = 0.002, 0.039) and the door to doctor arrival time (DAT) and the door to CT scan time (DCT) of the study group was significantly shorter (all p < 0.001). There were 49 patients (10.1%) and 33 patients (15.6%) from the control group and study group receiving thrombolysis, respectively. The DAT, DCT, imaging to needle time (INT), and door to needle time (DNT) of patients receiving thrombolysis in the study group were significantly shorter than that in the control group (all p < 0.01). The NIHSS in the study group after the thrombolysis was lower than that in the control group (p = 0.042). Conclusion No. 971 Hospital model can effectively shorten DAT, DCT, INT, and DNT, and improve the effectiveness of thrombolysis and prognoses of AIS patients.